DOCUMENTARY PRODUCTION: FISHERMEN MAKING A LIVING BEHIND THE PIK 2 WALL - Fitriyanto; Andi Setyawan; Fajar Muharam; Chepi Nurdiansyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The development of digital technology has brought significant changes in various aspects of the film industry, including cinematography. Cinematography as an important element in filmmaking plays a role in conveying messages, building atmosphere, and creating visual experiences for the audience. This research aims to analyze the transformation of cinematographic styles in Indonesian cinema in the digital era and identify the impact of technological developments on shooting techniques, lighting, visual composition, and post-production processes. The method used in this study is a qualitative method with a descriptive approach through literature studies from various journals, books, scientific articles, and relevant sources that discuss the development of Indonesian cinematography and cinema. The data obtained was analyzed to determine the changes in visual style that occurred before and after the use of digital technology in film production. The results show that the digital era has driven a more dynamic, flexible, and innovative transformation of cinematography styles. The use of high-resolution digital cameras, drone technology, camera stabilization devices, and modern editing software allows Indonesian filmmakers to produce better visual quality at a more cost-efficient cost. In addition, the development of digital technology also opens up opportunities for filmmakers to explore various visual styles that are more creative and in accordance with the needs of the film's narrative. Thus, the transformation of cinematography style in Indonesian cinema in the digital era not only improves the technical quality of film production, but also expands artistic possibilities in conveying stories to audiences.